2000
DOI: 10.1002/j.1556-6676.2000.tb02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Career Self‐Efficacy for Women: Evaluating a Group Intervention

Abstract: The study evaluated whether women participating in a career group designed to increase career-related self-efficacy would make gains on career decision-making self-efficacy and vocational exploration and commitment compared with women in a control group. Thir ty-one women participated in a 6-week treatment group, and 30 women participated in a no-treatment control group. Results indicated that, compared with the control group, women in the treatment group improved on career decision-making selfefficacy and voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 49 publications
2
86
0
9
Order By: Relevance
“…The authors hypothesized that as participants began to internalize their own personal role in their career decision process they then, began to be strengthen their confidence in making a career decision. Using Bandura's (1 986) components of self-efficacy as a framework, Sullivan and Mahalik (2000) designed an intervention to increase career decision self-efficacy for women. The authors put into practice a 6-week group career-counseling intervention designed explicitly using the four sources of efficacy information (i.e., performance accomplishment, vicarious learning, physiological arousal, and verbal persuasion).…”
Section: Results Of Uffelman and Colleagues' (2004) Study Demonstratementioning
confidence: 99%
See 1 more Smart Citation
“…The authors hypothesized that as participants began to internalize their own personal role in their career decision process they then, began to be strengthen their confidence in making a career decision. Using Bandura's (1 986) components of self-efficacy as a framework, Sullivan and Mahalik (2000) designed an intervention to increase career decision self-efficacy for women. The authors put into practice a 6-week group career-counseling intervention designed explicitly using the four sources of efficacy information (i.e., performance accomplishment, vicarious learning, physiological arousal, and verbal persuasion).…”
Section: Results Of Uffelman and Colleagues' (2004) Study Demonstratementioning
confidence: 99%
“…Within Sullivan and Mahalik's (2000) study, the control group consisted of 30 participants, 87% were European American, 7% were African American, 3% were Asian American, and 3% were Hispanic or Latinola. The median age within the control group was 20 years, and 56% were second-year students, 37% were third-year students, and 7%…”
Section: Results Of Uffelman and Colleagues' (2004) Study Demonstratementioning
confidence: 99%
“…Sullivan and Mahalik (2000) noted the importance of active support from group members . Therefore, support is one of the defining characteristics of a woman's group .…”
Section: Employment Counseling Interventions and Techniquesmentioning
confidence: 97%
“…These demands ranged from indecision about a major to social concerns. Although a review of studies focused on four-year colleges (Gerdes, & Mallinckrodt, 1994;Kahn, Nauta, Gailbreath, Tipps, & Chartrand, 2002;Korschgen & Hageseth, 1997;Leonard, 2002;Lewallen, 1993;Sullivan & Mahalik, 2000) indicated that an effective process aimed at helping undecided students from a practical and emotional perspective is lacking, the research on incoming undecided community college freshmen is sparse. Multon, Heppner, Gysbers, Zook & Ellis-Kalton (2001), however, found that, like their undergraduate college counterparts, community college students typically experienced varying degrees of anxiety when requesting career-counseling assistance.…”
Section: Research On Undecided Students' Negative Thinking Patternsmentioning
confidence: 99%